Kohesivitas Teman Sebaya dalam Konformitas Pada Remaja Sekolah - Martasari, Kartika; Arisandy, Desy (Jurnal Ilmiah Psyche, 2018)
his study aimed to determine the relationship betwen cohesivenees group and conformity peers in in students smk muhammadiyah 1 palembang. Dependent variable in this study is konformitas peers, while the kohesivitas kelompok an independent variable. Researched measuring instruments used the cohesivenees group scale and conformity peers scale. This research uses quantitative methods. The sample used in this study were 84 students of the SMK Muhammadiyah 1 Palembang. The results of this study found no significant association between group cohesiveness and conformity peers at SMK Muhammadiyah 1 Palembang with the value F = 21.541 , Adjusted R Square = 0.208 , p = 0.000 for the results of significance ( p ) 0,000 mean value of p < 0 , 05 . so stated there was a significant relationship